(untitled) (Journal of Informatics Education and Research, 2025)
Antisocial Personality Disorder (ASPD) and Substance Use Disorder (SUD) frequently co-occur, leading to severe behavioral, psychological, and social consequences. This study examines the comorbidity patterns and risk factors of ASPD and SUD among individuals receiving treatment in rehabilitation centers, psychiatric clinics, and de-addiction facilities in Dehradun, India. Using a purposive sampling method, 150 participants diagnosed with either or both disorders were assessed through structured clinical interviews and standardized psychological tools. Findings reveal a high prevalence of co-occurring ASPD and SUD, with males (78%) being disproportionately affected. Socioeconomic status, early childhood trauma, and impulsivity emerged as significant risk factors for dual diagnosis. Data analysis indicates a strong correlation between ASPD severity and substance dependency, particularly with alcohol and opioid use. Comparative analysis with previous studies suggests that the local prevalence rates align with national and global trends, highlighting the urgent need for targeted intervention strategies in Dehradun. The study underscores the importance of integrated mental health and substance abuse treatment programs to address comorbidity. It also provides policy recommendations for improving rehabilitation services in India. Future research should focus on longitudinal studies to explore the causal relationship between ASPD and SUD.